Experimental Study and Comparison with the Computational Study on Cooling of PV Solar Panel Using Finned Heat Pipe Technology. (2017) - Koundinya, Sandeep; Vigneshkumar, N.; Krishnan, A.S.
Abstract: Many solar energy utilizing techniques are present and PV modules are one among them which is having widespread applications. But, the main disadvantage of this is high cost and less efficiency. The efficiency of photovoltaic solar panel decreases with increase in operating temperature. This is because, the photo voltaic modules take only the visible light intensity for converting it to electrical energy and rest of the spectrum of light is converted to heat leading to the increase in operating temperature. Reflection from top surface is another reason for increase in operating temperature. The main aim of this project is to reduce the operating temperature using finned heat pipe. Experiments have been done on a prototype and the results have been compared with a computational study. Results have shown a maximum decrease of 13.8K by adopting this method. The results of experimental study and computational study are in good agreement.